Characterization of the Phytochemical Profile of Petroselinum Crispum Leaves in Central Kalimantan Habitat as a Basis for Pharmacological Potential Exploration - Nadia Dwi Nur Latifah; Noor Hujjatusnaini; Ridha Nirmalasari (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
This study aimed to characterize the phytochemical profile of Petroselinum crispum leaves cultivated in Central Kalimantan as a basis for exploring their pharmacological potential. P. crispum is a horticultural commodity of high economic value, widely used both as a culinary spice and in traditional medicine, making it a promising candidate for further development. The analysis focused on flavonoids, tocopherols, ascorbic acid, and estrogen content, using UV-Vis spectrophotometry. Results showed that flavonoid concentrations increased with higher quercetin standards, reaching a maximum of 0.92 mgQE/g at 100 µg/mL. In contrast, tocopherol and ascorbic acid levels declined as quercetin concentrations increased, suggesting that the compounds may have undergone degradation or interaction. Estrogen levels were recorded at 28.40 ng/mL with an absorbance of 0.498 and a regression equation of y = 0.0173x + 0.007 (R² = 0.998). The substantial flavonoid content and detectable estrogenic activity highlight P. crispum as a potential source of natural active compounds for antioxidant and hormonal therapy. These findings support the recommendation of P. crispum as a raw material for developing safe, affordable, and effective herbal supplements and phytopharmaceuticals to promote public health.